(untitled) (Universal International Scientific Journal, 2026)
This article analyzes in detail the development of English anthroponymy in the synchronic stage based on a linguoculturological approach. The study aims to identify religious, cultural, social and aesthetic motives that are active in the selection of modern English names. In particular, the influence of Puritan traditions, religious semantics, processes of abbreviation and combination, mass culture and fashion factors on the anthroponymic system is consistently highlighted. The results of the study show that in the synchronic stage, spiritual motives are relatively secondary in the selection of names, and the factors of tradition, resonance and socio-prestige are gaining priority.